Educational Activities of Wilhelm Andreas Rhenius (1753–1833) in Klaipėda and the First Lithuanian Translations of English Religious Literature - Strungytė-Liugienė, Inga (Knygotyra, 2021)
In the first half of the 19th century, the international interdenominational organization the Religious Tract Society in London provided financial support for the publication of religious books in the native languages of the people of the Kingdom of Prussia: German, Polish, Sorbian and Lithuanian. The branch of the Prussian Religious Tract Society established in Klaipėda, an important trading city of the time, took care of the translations of short books into Lithuanian along with their publishing and distribution. Wilhelm Andreas Rhenius (1753–1833), the inspector of the Bachman’s estate, the follower of the Moravian movement, who managed compilations, worked for the Klaipėda branch. This article aims to reveal the ties of Rhenius, the member of the Society, with the international organization in London, and his participation in educational activities in Klaipėda. Lithuanian translations of religious English texts patronized by the Religious Tract Society in London are also discussed, including an anonymous small volume book, The Warning Voice (Graudénimo Balsas, 1818), published in Tilsit, the Prussian Lithuania, in 4,000 copies, and the collected sermons Sixteen Short Sermons (Sźeßolika trumpi Kalbesei, 1820, Tilsit) by the British author Thomas Tregenna Biddulph (1763–1838), the minister of St. James’s Church in Bristol.
Keywords: the Religious Tract Society in Klaipėda; the Religious Tract Society in London; Wilhelm Andreas Rhenius; Robert Pinkerton; English religious literature; translations; surinkimininkai; the Moravian Church; Klaipėda in the 19th centur